2017
DOI: 10.18632/oncotarget.20919
|View full text |Cite
|
Sign up to set email alerts
|

High pretreatment plasma D-dimer predicts poor survival of colorectal cancer: insight from a meta-analysis of observational studies

Abstract: D-dimer, one of the canonical markers of hypercoagulability, was reported to be a potential prognostic marker of colorectal cancer. However, an inconsistent conclusion existed in several published studies. Thus, we performed this meta-analysis to provide a comprehensive insight into the prognostic role for pretreatment D-dimer in colorectal cancer. Six databases (English: Pubmed, Embase and Web of Science; Chinese: CNKI, Wangfang and VIP) were utilized for the literature retrieval. Hazard ratio (HR) was pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
(27 reference statements)
2
15
0
Order By: Relevance
“…15,16 Furthermore, high D-dimer levels have been associated with poor survival in patients with various malignancies, including pancreatic cancer. 17,18 In summary, our findings should inform guideline recommendations for high-risk patients, given the favorable risk-benefit ratio and convenience of the oral route of administration.…”
mentioning
confidence: 83%
“…15,16 Furthermore, high D-dimer levels have been associated with poor survival in patients with various malignancies, including pancreatic cancer. 17,18 In summary, our findings should inform guideline recommendations for high-risk patients, given the favorable risk-benefit ratio and convenience of the oral route of administration.…”
mentioning
confidence: 83%
“…18 Preoperative D-dimer is also reported to correlate with long-term oncological outcomes after colorectal cancer resection. [19][20][21][22] On univariate analysis in the present study, tumor stage correlated with postoperative D-dimer level.…”
Section: Discussionmentioning
confidence: 87%
“…D-dimer, which is produced when cross-linked fibrin is degraded by plasmin-induced fibrinolytic activity, is a useful indicator for hyper-coagulation. Many studies have affirmed that cancer patients with high PDL were more likely to have poor prognosis and aggressive characteristics (2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). To the best of our knowledge, this study is the first analysis using propensity score methods to assess the impact of preoperative PDL on outcomes for GC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that D-dimer can not only affect cellular signaling systems and promote cell proliferation, but also stimulate the cellular adhesion of tumor cells to endothelial cells, affect platelets and extracellular matrix, and ultimately, induce the growth and spread of tumors (3,4). Many studies have affirmed that high levels of plasma D-dimer were associated with advanced tumor stage and poor survival of cancer patients (5)(6)(7)(8)(9)(10)(11)(12). Several researches reported that preoperative plasma D-dimer level (PDL) was an independent prognostic factor in patients with completely resected nonsmall cell lung cancer (NSCLC) (5)(6)(7), and others confirmed that the prognosis was significantly influenced by the elevated PDL in patients with colorectal cancer (8)(9)(10), esophageal cancer (11), breast cancer (12) and so on.…”
Section: Introductionmentioning
confidence: 99%